Homeostasis - Hayward, Nick.; Collins, Cath.; Wilson, Elle.; Bertsa, Elenora (Hamilton, NJ Films for the Humanties & Sciences, 2009)
In this program we'll explore the concept of homeostasis. We'll ask what homeostasis is, why it is important, take a look at detecting changes from the stable state, counteracting changes from the stable state, and how homeostasis works.
Originally produced by VEA in 2008.
Narrator, Elle Wilson ; featuring, Elenora Bertsa.
DVD-R.
Closed captioned.
Keywords: Homeostasis; Biology -- Video Cassettes; Science -- Video Cassettes